Batik Sebagai Sarana Penanaman Nilai-Nilai Budaya Dan Pembentukan Karakter Bangsa - Shokiyah, Nunuk Nur (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2012)
Batik is one of the world heritage that was had the Indonesian nation and it is essential to be introduced to the younger generation. Batik is a technique of drawing, painting, or providing color on cloth to get a certain pattern and it was given color with tutup celup system. The process of batik is very detail, the procedure consist of Nglowong, nembok, medel, ngerok, bironi, ntogo, sag, washing, and pressing. The process of making batik so requires patience and precision to achieve optimal results. Batik activities are conducted continuously with direct or indirect that will affect the person's character. Character is influenced by environment such as social valuesÃ¢â‚¬â€¹Ã¢â‚¬â€¹, experience and education. Batik activities that were taught for children both in the school and the family will be very influential in the formation of the child character. Children are trained to be patient, thorough, and independent. Besides, it also helps children to learn more about own nation culture , then it can strengthen the nation character and itÂ  is as bastion of global culture influences.Â KeyÂ words: Batik, Cultural Velue, national character